DETERMINATION OF A BIOLOGICALLY ACTIVE COMPOUND OF KON- 1 IN BLOOD PLASMA BY METHOD OF HIGH-PERFOMANCE LIQUID CHROMATOGRAPHY WITH MINIMUM SAMPLE PRETREATMENTPROCEDURE: DEVELOPMENT AND VALIDATION OF THE METHOD, USE IN PRE-CLINICAL PHARMACOKINETIC RESEARCHES - E. A. Bulgakova; Yu. N. Karpenko (Сеченовский вестник)
The aim of this work was the development and validation of methods for determination of biologically active compound KOH-1 with proven nootropic activity in blood plasma by high performance liquid chromatography (HPLC) with ultraviolet detection (HPLC-UV). A simple, rapid and unlaborious procedure was proposed for sample preparation of plasma for chromatographic analysis, which ensures a high percentage of analyte extraction from the bioobject (more than 80%). Under the developed conditions, the lower limit of the quantitative determination of KOH-1 in plasma was 35 ng /ml. Estimated as a result of validation the precision of the method did not exceed 7%, the accuracy of the method was 93,5 - 112,8%. The developed bioanalytical technique was tested on blood samples of laboratory animals and humans and used in preclinical pharmacokinetic studies.